Creative collaborative experiences with interactive shadow theater - Marios Christoulakis; Andreas Pitsiladis; Petros Stergiopoulos; Nektarios Moumoutzis; Argiro Moraiti; Giannis Maragkoudakis; Stavros Christodoulakis (Pensa MultiMedia, 2014)
Storytelling is a very common educational practice that is used in every level of education. It has a positive impact in children's learning and creativity. Often the educational use of storytelling is based on national storytelling traditions such as Shadow Theater which is very popular in many countries including Greece. In this research we present eShadow, a storytelling tool inspired by the Greek traditional shadow theater and how it has been used in a number of Adult Learning Pilot Programmes (ALPPs) implemented within the context of the ALICE project in Greece. In these ALPPs, intra-family communication scenarios were investigated as well as scenarios related to enabling children develop their own digital stories using eShadow. Furthermore, eShadow was used in a live interactive performance event combining Music and Digital Shadow Theatre. The evidence gathered during the implementation of these ALPPs confirms that such kind of approaches can indeed enhance intergenerational bonding and create an engaging learning space for children to develop important key skills. Our findings illustrate that eShadow is very easy to use, attracts the interest of both children and teachers and has a positive impact on the development of children's creativity.